Constraints in acquiring and utilizing directors' experience: An empirical study of new‐market entry in the pharmaceutical industry. (16th January 2014) - Diestre, Luis; Rajagopalan, Nandini; Dutta, Shantanu
<x xml:space="preserve">Abstract</x> In this study we provide evidence that firms considering entering new markets are more likely to appoint directors with experience in those markets; and subsequently, we show that directors' market experience increases the likelihood of new‐market entry. Moreover, we explore the presence of constraints in both, acquiring experienced directors and utilizing their experience. Specifically, we find that experienced directors are less likely to join firms with financial restatements in the recent past as well as firms with a lower status than the firms where they currently serve. In addition, we find that interlocking directors' experience is less likely to lead to new‐market entry for firms that lack new‐product development experience and that exhibit a high level of market overlap with interlocked firms. Copyright © 2013 John Wiley & Sons, Ltd.